Optimization of Group Elevator Scheduling (International Journal of Engineering and Computer Science, 2017)
In this Generation Elevator has an vital role in day today human activities, Group elevator scheduling is efficient for mid-rise and high-rise buildings. This paper is to solve the group elevator scheduling problem with advance traffic information. A formulation is developed we can schedule the elevator processing based on the below priorities, first PIR sensor- This will be working based on the number of persons waiting for Elevator; second RFID Card reader-This is used to provide the priority to higher officials who carry this card to get the elevator faster; and finally Emergency Mode – Which will take the high priority among the elevator faster than the other signals. In existing, detailed car dynamics are embedded in simulation models for performance evaluation. Taking advantage of advance information, a new door action control method is suggested to increase the flexibility of elevators. In view of this existing system, all methods were combine together into a single process as mentioned above.